P115 Ovarian torsion in children: case report and discussion. (June 2019) - Stroiescu, Andreea; Byrne, Caoimhe; Hennebry, Jennifer; Bolger, Mark; Sheikh, Yusra; Stepien, Julita
Abstract : Ovarian torsion is an uncommon cause of acute abdominal pain in the paediatric population and extremely rare in early childhood. The presentation can be non-specific, mimicking other pathologies such as acute appendicitis, resulting in diagnostic delay. The aetiology, diagnosis and management can differ from those in adults. Misdiagnosis of adnexal torsion is not uncommon in children and may cause loss of the ovary or fallopian tube. In the case of acute abdominal pain, ultrasonography is usually the most routinely used diagnostic tool, alongside colour-Doppler for evaluation of blood circulation in the ovarian pedicle. With the aid of a case report we will discuss the common presentation and examination findings of adnexal torsion along with the causes and risk factors. We will illustrate the normal adnexal anatomy and show the common imaging findings of ovarian torsion. Further imaging and management options will also be reviewed. The literature has reported up to an 80–90% rate of ovarian salvage with early intervention. Early and accurate diagnosis of ovarian torsion and early intervention with restoration in blood flow is imperative in avoiding irreversible damage to the ovary and long term fertility issues.